Алгебра 8 класс Ю.Н.Макарычев, Н.Г.Миндюк, К.И.Нешков, С.Б.Суворова

Алгебра 8 класс Ю.Н.Макарычев, Н.Г.Миндюк, К.И.Нешков, С.Б.Суворова

авторы: , , , .
издательство: "Просвещение" 2013 г

Раздел:

Номер №98

Упростите выражение:
а)
$\frac{1}{a - 4b} - \frac{1}{a + 4b} - \frac{2a}{16b^2 - a^2}$
;
б)
$\frac{1}{2b - 2a} + \frac{1}{2b + 2a} + \frac{a^2}{a^2b - b^3}$
.

Решение а

$\frac{1}{a - 4b} - \frac{1}{a + 4b} - \frac{2a}{16b^2 - a^2} = \frac{a + 4b - (a - 4b) + 2a}{(a - 4b)(a + 4b)} = \frac{2a + 8b}{(a - 4b)(a + 4b)} = \frac{2(a + 4b)}{(a - 4b)(a + 4b)} = \frac{2}{a - 4b}$

Решение б

$\frac{1}{2b - 2a} + \frac{1}{2b + 2a} + \frac{a^2}{a^2b - b^3} = \frac{1}{2(b - a)} - \frac{1}{2(b + a)} - \frac{a^2}{b(b^2 - a^2)} = \frac{b(b - a) - b(b - a) - 2a^2}{2b(b - a)(b + a)} = \frac{b^2 + ab - b^2 + ab - 2a^2}{2b(b - a)(b + a)} = \frac{2ab - 2a^2}{2b(b - a)(b + a)} = \frac{2a(b - a)}{2b(b - a)(b + a)} = \frac{a}{b(b + a)}$